COST AND QUALITY IN THE EDUCATION PROCESS - Warisno, Andi (UIN Ar-Raniry, 2017)
Although educationcost is not the only factor to create quality,a good education process is highly determined by the sufficiency of funds. Cost is one of the resources that directly supports the effectiveness and efficiency of education management. The higher the education cost spent, the greater the quality of education that one will experience.